The flow dynamics behind a flexible finite cylinder as a flexible agitator - Yong, T.; Chan, Hiang; Dol, Sharul; Wee, Siaw khur; Kumar, P. (2017)
© Published under licence by IOP Publishing Ltd. This paper investigates the flow dynamics behind a flexible finite cylinder in a single-phase flow using a water tunnel. The cylinder was individually submerged in water at Re D = 4000, 6000 and 8000. The cylinder investigated has a AR = 10 and 16 and is made of EVA in order to achieve the lower stiffness for flexibility. A same AR of its aluminium rigid cylinder was investigated to serve as a benchmark to the flow dynamics behind a flexible cylinder. The results the downwash that hinders the transportation of vortices to the downstream was diminished. As a direct consequence of this phenomenon, the turbulence production has seen significant improvement for flexible finite cylinder.